Leadership On Employee Performance - Ema Yudiani; Zarkasi Zarkasi; Huzaemah Huzaemah; Rachmad Ilham; I Nyoman Tri Sutaguna (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to investigate and evaluate the influence of leadership style and work ethic on workplace interactions. The response sample consisted of around 32 students. The data was collected via sending questionnaires to respondents. Multiple regressive lining is the method of analysis used. When the results of the investigation are positive and suggestive of the patient's responsiveness. The T-Test exposes this as